2011
DOI: 10.1182/blood-2010-06-293167
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of Hspa9, a del(5q31.2) gene, results in a decrease in hematopoietic progenitors in mice

Abstract: IntroductionThe myelodysplastic syndromes (MDS) are a group of clonal hematopoietic disorders exhibiting ineffective hematopoiesis characterized by peripheral blood cytopenias. Whole chromosome 5 loss or interstitial deletions spanning 1 copy of 5q31.2 are among the most common abnormalities detected by conventional cytogenetic analysis in de novo (6%-20% of patients) and therapyrelated MDS (up to 40% of patients). [1][2][3] The commonly deleted segment in 5q31.2 has been mapped, 4,5 and mutational analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 49 publications
1
53
0
Order By: Relevance
“…11,12 It has been shown that mortalin KD impairs erythroid differentiation and reduces the number of colony-forming progenitor cells in the murine BM. 38 However, the precise role of mortalin in HSC maintenance has yet to be clarified. Here, we examined mortalin KD and mortalin-OE HSCs, and showed that mortalin is critical for the preservation of HSC faculties under both ex vivo culture and in vivo transplantation conditions.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 It has been shown that mortalin KD impairs erythroid differentiation and reduces the number of colony-forming progenitor cells in the murine BM. 38 However, the precise role of mortalin in HSC maintenance has yet to be clarified. Here, we examined mortalin KD and mortalin-OE HSCs, and showed that mortalin is critical for the preservation of HSC faculties under both ex vivo culture and in vivo transplantation conditions.…”
Section: Discussionmentioning
confidence: 99%
“…55 Subsequently, several more 5q-CDR-encoded genes including microRNAs miR145 and miR146a have been implicated in the pathogenesis and clinical presentation of MDS. [56][57][58][59] Unfortunately, investigation of genes in the MDS-associated CDRs of chromosomes 20q and 7q have been less conclusive, and the pathogenic mechanisms associated with these and other recurring chromosomal abnormalities remain unknown.…”
Section: Advances In the Genetic Basis Of Mdsmentioning
confidence: 99%
“…16 Reduced expression of HSPA9 in primary human CD34 ϩ cells results in delayed erythroid maturation and increased apoptosis in vitro and decreased hematopoietic progenitors in mice. 17 Npm ϩ/Ϫ mice develop erythroid macrocytosis, megakaryocytic dysplasia, and are predisposed to myeloid malignancies (AML and MPNs) at 10-24 months of age. 18 Finally, Apc ϩ/Ϫ mice have alterations in their stem cell compartment with concomitant changes in cell cycle and apoptosis which may be relevant for MDS.…”
Section: Karyotype Abnormalities In Mds and Gene Haploinsufficiencymentioning
confidence: 99%